2006
DOI: 10.1073/pnas.0510007103
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements have contributed to thousands of human proteins

Abstract: This is a report of many distant but significant protein sequence relationships between human proteins and transposable elements (TEs). The libraries of human repeated sequences contain the DNA sequences of many TEs. These were translated in all reading frames, ignoring stop codons, and were used as amino acid sequence probes to search with BLASTP for similar sequences in a library of 25,193 human proteins. The probes show regions of significant amino acid sequence similarity to 1,950 different human genes, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 9 publications
2
43
0
Order By: Relevance
“…Despite the conservative nature of our analysis, we found compelling evidence for TE insertion into expressed protein-coding sequences. Our results reside between two extremes, represented by human studies, which claim that more than 1000 proteins contain TE sequence (Nekrutenko and Li 2001;Britten 2006), and Drosophila melanogaster, which seems to possess very few expressed TE-gene chimeras (Lipatov et al 2005). With very few exceptions (e.g., Gotea and Makalowski, 2006;Bundock and Hooykaas 2005), the directionality of these relationships (contribution or co-option of genic regions by TEs) has not been determined.…”
Section: Implications Of the Methods And Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Despite the conservative nature of our analysis, we found compelling evidence for TE insertion into expressed protein-coding sequences. Our results reside between two extremes, represented by human studies, which claim that more than 1000 proteins contain TE sequence (Nekrutenko and Li 2001;Britten 2006), and Drosophila melanogaster, which seems to possess very few expressed TE-gene chimeras (Lipatov et al 2005). With very few exceptions (e.g., Gotea and Makalowski, 2006;Bundock and Hooykaas 2005), the directionality of these relationships (contribution or co-option of genic regions by TEs) has not been determined.…”
Section: Implications Of the Methods And Resultsmentioning
confidence: 79%
“…But with homology data alone, we cannot infer the direction of the relationship. That is, did TEs contribute sequence to exons, thus providing potentially adaptive material, as has been widely argued (Britten 2006;Cordaux et al 2006), or did TEs co-opt genic sequence, as has been demonstrated previously (Jiang et al 2004;Lai et al 2005)? Although the direction of sequence relationship can be difficult to decipher, gene family phylogenies can provide insight (Gotea and Makalowski 2006).…”
Section: Functional Biases Of Genes With Homology To Tesmentioning
confidence: 82%
See 1 more Smart Citation
“…G72 represents a rare case of a primate-specific gene, 3,5 it shows a complex alternative splicing pattern and some unusual genomic features that may be related to its rapidly evolving structure. 6,29 The gene is expressed at relatively low levels in the adult brain, although the pattern and level of its expression during development is still uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 The gene is located within a genomic region enriched in repeat elements, and a part of its coding sequence and 5 0 flanking region have been derived from long terminal repeat elements (http://genome.ucsc.edu). 6 G72 shows a complex alternative splicing pattern, and several splicing isoforms have been described. Among them, LG72 presents the longest open reading frame 3,7 and is the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%